1973
DOI: 10.1021/es60085a012
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and loss of methylmercury-203 by bluegills (Lepomis macrochirus)

Abstract: to imply that both samples have the same origin, since this is unlikely; however, the analysis shows that the sample was definitely a No. 6 fuel oil. ConclusionWe have recorded infrared spectra of over 50 different petroleum samples; absorptivities of 21 bands between 650 and 1200 cm™1 can be used to characterize the samples. Stored in a computer file, the 21 absorptivities of every known sample can be compared with those of any unknown sample at a later date. Using the ratios of known to unknown absorptivitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 4 publications
1
23
0
Order By: Relevance
“…5) is in accordance with similar findings In both fish (Burrows & Krenkel 1973, Olson e t al. 1978) and mammals (Norseth & Clarkson 1971, Rabenstein 1978.…”
Section: Fish Experimentssupporting
confidence: 92%
“…5) is in accordance with similar findings In both fish (Burrows & Krenkel 1973, Olson e t al. 1978) and mammals (Norseth & Clarkson 1971, Rabenstein 1978.…”
Section: Fish Experimentssupporting
confidence: 92%
“…Whether there was any biotransformation (methylation and demethylation) within the fish body was not revealed by our study. Pennacchioni et al (1976) suggested that fishes are unable to methylate Hg in vivo, whereas other studies indicated that methylation and demethylation are possible (Burrows & Krenkel 1973, Simon & Boudou 2001). We found a significant difference in the AE, the uptake rate constant, and the elimination rate constant between Hg(II) and MeHg.…”
Section: Discussionmentioning
confidence: 99%
“…gills, brains, viscera) has not been extensively quantified. There is some evidence of considerable methylation and demethylation in fish muscle (Burrows & Krenkel 1973, Simon & Boudou 2001, although some studies have also indicated that fishes are unlikely to methylate the inorganic Hg to MeHg within their tissues in vivo (Pennacchioni et al 1976).…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
See 1 more Smart Citation
“…Aqueous mercury levels are affected by many factors including oxygen concentration, precipitation, temperature, water level, and wetland runoff (Sellers et al 2001, Hurley et al 1998a, Regnell et al 1997. Although less variation would be expected in fish muscle tissue (Downs et al 1998, Foster et al 2000, where the biological half life of mercury can be one to three years (McKim et al 1976, Burrows andKrenkel 1973), at least one study suggests substantial seasonal variation in fish tissue mercury as a possible consequence of variations in mercury uptake (Park and Curtis 1997). Also, localized aggregations of fish from the same water body may exhibit significant spatial variations in mercury concentration as a likely result of differences in mercury bioavailability among foraging areas (Munn and Short 1997).…”
Section: Mercury Bioaccumulation Factors For Savannah River Fish Intrmentioning
confidence: 99%